PERALIHAN HAK ATAS TANAH DENGAN AKTA JUAL BELI YANG DILANGSUNGKAN DENGAN ITIKAD TIDAK BAIK - Sartika , Dwi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The numerous cases of land rights transfer with malicious intent indicate a legal loophole exploited by organizations or individuals for personal gain. Dishonest actions can manipulate transactions due to the unclear legal boundaries surrounding the transfer of land rights. The transfer of land rights requires valid evidence in the form of land certificates, obtainable only through the registration of land rights. Unethical practices in land transfer can have negative social and economic impacts. The normative legal research method is an approach in the legal science that examines legal norms. In the study of the Court Decision Number 249/Pid.B/2022/Pn.Jkt.Brt, the normative juridical method is used with a doctrinal legal research or document study approach, divided into legal and case approaches. Land certificates provide legal protection and clarity by identifying the rights holder and subject. Household assistant Nirina Zubir committed land certificate fraud, violating Article 28H of the 1945 Constitution, which prohibits arbitrary seizure of personal property. The validity of agreements depends on lawful cause and good faith. Identity forgery in Decision No. 60/Pdt/2018/PT.Btn indicates the lack of precision by Notaries/PPAT, resulting in unfulfilled objective requirements. The transfer of land rights requires good faith in accordance with regulations; land certificates offer legal certainty, protection, and are crucial in the transfer process. Certificate fraud is a criminal act with dismissal sanctions, and the professional ethics of PPAT are crucial.